The Effect of Various Media and Hormones via Suspension Culture on Secondary Metabolic Activities of (Cape Jasmine) Gardenia jasminoides Ellis - Reza Farzinebrahimi; Rosna Mat Taha; Kamaludin Rashid; Jamilah Syafawati Yaacob (The Scientific World Journal)
The leaf of Gardenia jasminoides Ellis was used as explants and was cultured on MS and WPM media supplemented with various concentrations of NAA, IAA, 2,4-D, IBA, TDZ, and Kn (0 to 5 mg L−1 with 0.5 increment). After six months, the higher percentage of callus (100%) and the best dry and fresh weight of callus were formed on WPM medium supplemented with 2,4-D and NAA (2.0-3.0 mg L−1) and this amount was decreased from (84%) to (69%) when this media supplemented with Kinetin and TDZ (1 mg L−1) respectively were used. Leaf segments cultured on WPM media added with Kn (1 mg L−1) and TDZ (2 mg L−1) yielded the least amount of callus. It was found that WPM media added with IAA (4.5–5.0 mg L−1) were optimum for root induction from G. jasminoides plantlets. Antibacterial screening of leaf extracts (in vivo) showed no inhibitory effect against E. coli, P. aeruginosa, S. aureus, and B. cereus, in contrast to callus extracts from leaf cultures supplemented with NAA, which showed inhibition activity against E. coli and B. cereus. The callus extracts from leaf cultures grown on both MS and WPM media showed higher antioxidant and superoxide dismutase activities than leaf extracts.